Analisis Penerapan ISO 9001:2000 dengan Six Sigma Berbasis Biaya Kualitas pada PT Honda Precision Parts Manufacturing - Sigit Hermawan; Mariya Ulfa (Universitas Negeri Surabaya, 2018)
The purpose of this research is to know how big the role of ISO 9001:2000 to a company that has been applied using cost-based approach to six sigma quality. ISO 9001:2000 is a standard on quality management. With the implementation of ISO 9001:2000 is to determine its effect on fee levels of quality. Where quality costs are the costs accrued or incurred to prevent and improve the quality of which occur as a result of not reaching the specifications of products or services that have been set. The analytical tool used in Six Sigma approach is the number of defects each year in each production department so it can know which department has the largest number of product failure as compared with total production in which the department will be the object of research. Besides, the cost of the quality of the department which has the largest defects will be analyzed to determine the total effectiveness of the department. The results of this study is the successful application of ISO 9001:2000 at PT Honda Precision Parts Manufacturing measured using six sigma where sigma approach in the year 2004-2009 has increased. As for the cost of quality is itself an increase in the cost of prevention and appraisal costs. This shows an improvement in terms of quality has been going well. Based on the above information, it can be concluded that the increase in sigma and increased costs of prevention and appraisal costs are not separated from the role of ISO 9001:2000 which has been applied. It is evident that any improvements made as specified in ISO 9001:2000 concept will cause a rise in the cost of some components in the calculation of quality costs, but improvements are made will affect the production of goods falling NG or defect that ultimately reduce overall quality costs.